2020
DOI: 10.1136/jitc-2020-001117
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index (BMI) and outcome of metastatic melanoma patients receiving targeted therapy and immunotherapy: a multicenter international retrospective study

Abstract: BackgroundObesity is a risk factor for malignancy; however, its prognostic role in patients with metastatic melanoma is controversial. We aim to investigate the prognostic role of body mass index (BMI) in patients with metastatic melanoma receiving mitogen-activated pathway kinase inhibitors (MAPKi), immune checkpoint inhibitors (ICIs) alone or their sequence.MethodsData on patients with metastatic melanoma receiving ≥1 line of systemic treatment were retrieved from prospectively collected databases. Progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 16 publications
2
32
1
7
Order By: Relevance
“…The remaining 26 studies were subsequently reviewed and screened according to our inclusion and exclusion criteria. Finally, 18 studies were included in our systematic review ( Figure 2 ) [ 18 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. The included studies were published between 2018 and 2020, and were retrospective studies, either single or multicenter; one study was a pooled analysis of patients treated with immunotherapy in the context of phase 2 and 3 trials.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The remaining 26 studies were subsequently reviewed and screened according to our inclusion and exclusion criteria. Finally, 18 studies were included in our systematic review ( Figure 2 ) [ 18 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. The included studies were published between 2018 and 2020, and were retrospective studies, either single or multicenter; one study was a pooled analysis of patients treated with immunotherapy in the context of phase 2 and 3 trials.…”
Section: Resultsmentioning
confidence: 99%
“…The study by McQuade et al is the only large multicenter study ( n = 331) supporting a positive association of high BMI with improved outcomes, however only in male patients receiving anti-PD1 or PD-L1 (PFS HR 0.69 (95% CI 0.45–1.06), p = 0.07; OS HR 0.69 (95% CI 0.42–1.12); p = 0.84) [ 18 ]. Overall, two studies, making the largest sample size (total n = 704), reported no association of BMI with disease response and survival [ 21 , 24 ]. In the study by Rutkowski et al, BMI was not associated with disease control rate (DCR) (adjusted OR 0.98 (95% CI 0.93–1.03); p = 0.432), PFS (HR 1.00 (95% CI 0.98–1.03) p = 0.732), nor OS (HR 1.02 (95% CI 0.99–1.05); p = 0.202) [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Beyond its well-known role as a risk factor for the development of RCC, obesity is also emerging as a potential key factor for response to therapy [ 3 ]. A growing body of evidence suggests that being overweight and obese are associated with better outcome in cancer patients treated with immunotherapy [ 4 , 5 ]. In this regard, Sanchez et al investigated the angiogenic and immunologic transcriptomic profiles of the primary tumor and perinephric adipose tissue in normal weight and obese RCC patients.…”
Section: Introductionmentioning
confidence: 99%